Travel Constraints, Trust, Travel Motivation and Travel Intention : : A Case Study of Covid 19 Pandemic - Foedjiawati Foedjiawati; Fransisca Andreani; Njo Anastasia (Jurnal Manajemen Perhotelan dan Pariwisata, 2023)
The limitation of traveling refers to individual limitations; namely, interpersonal and intrapersonal constraints. However, trust shapes the traveler’s confidence to travel. Furthermore, travelers need motivation as their push factor to appeal their interest in traveling. This study aims to explore the relationship between travel constraints and trust on travel intention and travel motivation as the mediating variable. The sample was determined by using purposive sampling on Indonesia’s travelers who travelled during the Covid-19 pandemic, from March 2020 to February 2021 using online questionnaire. Results indicated that the intrapersonal constraint had positive effects on travel intention and travel motivation. On the other hand, interpersonal constraints and trust did not affect travel intention nor travel motivation. Therefore, the research results imply a positive contribution to the collaborative development theories between Theory Planned Behavior and those related in tourism sector. Leaders in tourism business sectors could plan their marketing strategies in a fast-changing pace in the world such as, the crises of Covid-19 pandemic to bring people’s motivation out in order to be interested in traveling again although with several terms and conditions after the human mobility was curtailed.